THE TRANSFORMATIVE EFFECTS OF ARTIFICIAL INTELLIGENCE AND UNMANNED AERIAL VEHICLES ON NATIONAL DEVELOPMENT PARADIGMS - Kudrat Saidkulovich Ortikov (Sciental Journals Publishing, 2025)
In recent years, the integration of artificial intelligence (AI) with unmanned aerial vehicles (UAVs) has led to significant advancements across various fields. This comprehensive analysis explores the dynamically evolving landscape of AI-enabled UAVs, as well as the concept of "friendly" (environmentally conscious) applications and computing within the context of their use. The work encompasses promising trends, futuristic concepts, and the associated challenges inherent in this domain. This study examines the role of AI in enabling navigation, object detection and tracking, wildlife monitoring, enhancing agricultural precision, facilitating rescue operations, and carrying out surveillance activities and establishing communication between UAVs using environmentally oriented computing methods. By analyzing the interaction between AI and UAVs, this work highlights the potential of these technologies to radically transform sectors such as agriculture, surveillance systems, and emergency management strategies. Beyond predicting opportunities, the review also considers ethical considerations, safety concerns, the necessity of developing regulatory frameworks, and the responsible deployment of AI-enhanced UAV systems. By summarizing the research findings in this area, this review contributes to an understanding of the evolving landscape of AI-powered UAVs and establishes a foundation for further research in this promising field.
Keywords: Artificial intelligence, unmanned aerial vehicles (UAVs), monitoring, surveillance, computing